Solvent‐Dependent Self‐Assembly Behaviour and Speciation Control of Pd6L8 Metallo‐supramolecular Cages. Issue 14 (3rd March 2014) - Henkelis, James J.; Fisher, Julie; Warriner, Stuart L.; Hardie, Michaele J.
Abstract The C3‐symmetric chiral propylated host‐type ligands (±)‐tris(isonicotinoyl)‐tris(propyl)‐cyclotricatechylene (L1) and (±)‐tris(4‐pyridyl‐4‐benzoxy)‐tris(propyl)‐cyclotricatechylene (L2) self‐assemble with PdII into [Pd6L8]12+ metallo‐cages that resemble a stella octangula. The self‐assembly of the [Pd6(L1)8]12+ cage is solvent‐dependent; broad NMR resonances and a disordered crystal structure indicate no chiral self‐sorting of the ligand enantiomers in DMSO solution, but sharp NMR resonances occur in MeCN or MeNO2. The [Pd6(L1)8]12+ cage is observed to be less favourable in the presence of additional ligand, than is its counterpart, where L=(±)‐tris(isonicotinoyl)cyclotriguaiacylene (L1 a). The stoichiometry of reactant mixtures and chemical triggers can be used to control formation of mixtures of homoleptic or heteroleptic [Pd6L8]12+ metallo‐cages where L=L1 and L1 a.